ONE DONOR EGG AND “A DOLLOP OF LOVE”: THE BANAL AMBIGUITIES OF EGG DONATION ADVERTISING ON FACEBOOK - Kant, Tanya; Reed, Elizabeth (AoIR Selected Papers of Internet Research, 2020)
Using textual analysis of 28 adverts for egg donation, sharing, and freezing drawn from Facebook’s Ad Library archive, we consider what forms of motherhood, kinship, and sociality are promised through targeted advertisements for Assisted Reproductive Technologies (ARTs) on Facebook. We seek to understand (1) how egg donation, sharing and freezing adverts by ART providers represent the women they expect to use their services; (2) how the meaning of these representations is changed by their delivery through algorithmically targeted marketing; and (3) what imaginative, genealogical, and relational possibilities are foreclosed or endorsed in the delivery of these adverts to algorithmically anticipated “fertile females”. Through textual analysis we seek to understand the forms of potential “life” that are present in the advertisements. We consider the representations of egg donation, identify a banal ambiguity in promised post-feminist kinship, and identify the selected families-in-making which might be created by ART. We combine this with a critical interrogation of how and why these adverts are targeted and delivered to certain demographics of algorithmically anticipated Facebook users. The opacity and structural rigidity of Facebook’s targeted advertising systems – structural mechanisms that are binaric in back-end databases and yet “lively” at the point of the user interface - require that we interrogate both media text and computational delivery mechanisms to meaningfully understand what forms of “life” are promised by gender-targeted ART. The genealogical possibility offered through ART is represented with banal ambiguity wherein potentially disruptive arrangements of kinship are derisked by an overarching narrative of simplicity and sameness.